Sustainable development of the Amazonbasin in the Andean Environmental Agenda - Rodríguez Quiñónez, Denisse (2012)
This article establishes how the Andean Environmental Agenda 2006-2010, as the first effort for including environmental issues in the communitarian agenda, formulates policies and actions for promoting sustainable development in the Amazon basin, through the review of its three thematic areas: biodiversity, climate change and hydrical resources.